2019
DOI: 10.1111/eva.12764
|View full text |Cite
|
Sign up to set email alerts
|

Reaction norm analysis reveals rapid shifts toward delayed maturation in harvested Lake Erie yellow perch (Perca flavescens)

Abstract: Harvested marine fish stocks often show a rapid and substantial decline in the age and size at maturation. Such changes can arise from multiple processes including fisheries‐induced evolution, phenotypic plasticity, and responses to environmental factors other than harvest. The relative importance of these processes could differ systematically between marine and freshwater systems. We tested for temporal shifts in the mean and within‐cohort variability of age‐ and size‐based maturation probabilities of female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…In study lakes with an incidental Yellow Perch harvest, it is likely that exploitation would be skewed towards mature females based on sex and maturity data collected in this study, similar to patterns that have been found or predicted to occur based on dimorphic growth in other lakes in the Upper Midwest (Isermann 2007;Schoenebeck and Brown 2011;Uphoff and Schoenebeck 2012). Yellow Perch exploitation has been correlated with a truncated size distribution, a decline in recruitment, and earlier maturation (Marsden and Robillard 2004;Lauer et al 2008;Gíslason et al 2019), so a more thorough assessment of the effects of harvest, including incidental catch in lakes with a small size structure, may be warranted in future studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In study lakes with an incidental Yellow Perch harvest, it is likely that exploitation would be skewed towards mature females based on sex and maturity data collected in this study, similar to patterns that have been found or predicted to occur based on dimorphic growth in other lakes in the Upper Midwest (Isermann 2007;Schoenebeck and Brown 2011;Uphoff and Schoenebeck 2012). Yellow Perch exploitation has been correlated with a truncated size distribution, a decline in recruitment, and earlier maturation (Marsden and Robillard 2004;Lauer et al 2008;Gíslason et al 2019), so a more thorough assessment of the effects of harvest, including incidental catch in lakes with a small size structure, may be warranted in future studies.…”
Section: Discussionsupporting
confidence: 75%
“…2008; Gíslason et al. 2019), so a more thorough assessment of the effects of harvest, including incidental catch in lakes with a small size structure, may be warranted in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these impacts on population abundance, there is growing evidence that harvesting can lead to phenotypic changes in fish populations (Gislason et al, 2019;Kuparinen & Merila, 2007;Palkovacs, 2011). Fisheries are often size-selective for the largest and most mature individuals in the stock, which can inadvertently select for a smaller size and/or lower age at maturity (Kuparinen et al, 2016;Kuparinen & Merila, 2007;Law, 2000;Palkovacs, 2011;Sharpe & Hendry, 2009), increased reproductive investment (Hutchings & Fraser, 2008) and increased somatic growth (Devine et al, 2012).…”
Section: Introductionmentioning
confidence: 99%